Grain Price Spikes and Beggar-thy-Neighbor Policy Responses : A Global Economywide Analysis - Jensen, Hans G. (Published by Oxford University Press on behalf of the World Bank, 2018)
When prices spike in international grain markets, national governments often reduce the extent to which that spike affects their domestic food markets. Those actions exacerbate the price spike and international welfare transfer associated with that terms of trade change. Several recent analyses have assessed the extent to which those policies contributed to the 2006–08 international price rises but only by focusing on one commodity or by using a back-of-the envelope (BOTE) method. The present more comprehensive analysis uses a global, economy-wide model that is able to take account of the interactions between markets for farm products that are closely related in production and/or consumption and able to estimate the impacts of those insulating policies on grain prices and on the grain trade and economic welfare of the world's various countries. Our results support the conclusion from earlier studies that there is a need for stronger WTO disciplines on export restrictions.